Immunotherapeutic approaches in prion disease: progress, challenges and potential directions. (May 2013) - Brazier, Marcus W; Mot, Alexandra I; White, Anthony R; Collins, Steven J
Therapeutic trials utilizing animal models of prion disease have explored a variety of compounds and a number of approaches with varying success, including several immunotherapeutic strategies, such as passive immunization through the delivery of viruses carrying nucleic acid inserts encoding prion protein-specific immunoglobulin. Targeted, organ-specific cellular production of therapeutic proteins is a relatively unexplored approach in the treatment of neurodegeneration despite many successful experimental outcomes in animal models and human trials of other diseases of the CNS. Emphasizing studies utilizing mouse models of disease, this review outlines developments and limitations of immunological approaches to the treatment of prion diseases. In addition, the authors discuss the potential of an experimental therapeutic strategy, utilizing hybridoma cells injected directly into the CNS to establish long-term production of anti-prion antibodies in vivo within the organ associated with the greatest pathogenic change in prion disease, the brain.